2017
DOI: 10.1039/c7ce01252g
|View full text |Cite
|
Sign up to set email alerts
|

Halogen bonded cocrystals of active pharmaceutical ingredients: pyrazinamide, lidocaine and pentoxifylline in combination with haloperfluorinated compounds

Abstract: Six novel halogen-bonded cocrystals of active pharmaceutical ingredients with 1,4-diiodo- and 1,4-dibromotetrafluorobenzene have been synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Where large quantities of halogen-bonded materials are desired (>100 mg), crystallization methods requiring solvent evaporation or solvent diffusion can be tedious to perform, often requiring many days or perhaps weeks to achieve the desired product in sufficient quantity. Mechanochemistry has been shown to be a favorable route for the halogen bond synthon, 54,59,60,61,62 offering a scalable and rapid method of preparing halogen-bonded cocrystals, 63,64 all without the need of large volumes of solvents. However, mechanochemistry by ball milling 65 has the inconvenience of yielding powdered products, requiring further manipulations in order to prepare a sample for SCXRD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Where large quantities of halogen-bonded materials are desired (>100 mg), crystallization methods requiring solvent evaporation or solvent diffusion can be tedious to perform, often requiring many days or perhaps weeks to achieve the desired product in sufficient quantity. Mechanochemistry has been shown to be a favorable route for the halogen bond synthon, 54,59,60,61,62 offering a scalable and rapid method of preparing halogen-bonded cocrystals, 63,64 all without the need of large volumes of solvents. However, mechanochemistry by ball milling 65 has the inconvenience of yielding powdered products, requiring further manipulations in order to prepare a sample for SCXRD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Choquesillo-Lazarte et al [ 247 ] has investigated the nature of halogen bonding interactions observed in pharmaceutical cocrystals of pyrazinamide, lidocaine and pentoxifylline with perfluorinated halogen-bond donors namely 1,4-diiodotetrafluorobenzene (tfib) and 1,4-dibromotetrafluorobenzene [ 247 ]. The halogen bonding interaction observed in lidocaine-1,4-diiodotetrafluorobenzene (2:1) and lidocaine-1,4-dibromotetrafluorobenzene (2:1) cocrystals are shown in Figure 16 .…”
Section: Influence Of Intermolecular Interactions On Cocrystallizamentioning
confidence: 99%
“…To a prevailing degree, however, when noncovalent interactions are concerned, hydrogen bonding (HB) [19] is implied [20]. Considering that over the last decade, the halogen bond (XB) [21] has emerged as an effective tool for crystal engineering [22][23][24][25][26][27][28][29] and designing supramolecular constructs [30][31][32], it is surprising that literature reports on the utility of XB in engineering new API crystal forms has been relatively scarce [20,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…To a prevailing degree, however, when noncovalent interactions are concerned, hydrogen bonding (HB) [19] is implied [20]. Considering that over the last decade, the halogen bond (XB) [21] has emerged as an effective tool for crystal engineering [22][23][24][25][26][27][28][29] and designing supramolecular constructs [30][31][32], it is surprising that literature reports on the utility of XB in engineering new API crystal forms has been relatively scarce [20,[33][34][35][36]. Our recent engagement in crystal engineering based on XB in metal complexes [37][38][39][40][41][42][43][44][45] prompted us to consider exploring new opportunities for filling the above void and applying the XB approach towards identifying novel API crystal forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation